A Student Grading and Information Management System of Wat Sangwonpimonpaiboon (Janthanukul) School - บุญมาก พรนิภา; สมุทรักษ์ วรพรต; พวงแก้ว จิรวดี; วงษ์ทองดี พายุ; ภุมรินทร์ วัฒนชัย (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research presents the development of a Student Grade and News Management System for Wat Sangwon Pimonpaiboon (Chantanukul) School. The primary objectives are to facilitate the management of academic performance, streamline the school’s public relations operations, and systematize data storage. This development aims to mitigate the risk of data damage or loss while enhancing overall administrative efficiency. The system was developed as a web application using Visual Studio Code, with XAMPP serving as the local server environment and database management tool. The system’s architecture is divided into three main user modules: 1) The Administrator module, which allows users to add, delete, edit, and search personnel, student, and academic records, as well as manage school news via the website; 2) The Teacher module, enabling teachers to manage student information and academic results; and 3) The Homeroom Teacher module, which allows them to monitor students’ academic progress and generate official grade reports. The results demonstrated that the developed system is highly practical for actual deployment within the school. It significantly increases operational convenience and speed by reducing the procedures and time required for managing academic records and school announcements. A usability test conducted with five teachers and school staff members revealed an overall user satisfaction mean score of 4.40. The participants strongly agreed that implementing this system would greatly improve the speed and accuracy of academic and news management. This system can be considered a catalyst for shifting traditional school practices towards adapting to the changing world of the digital age.